Almanaques sí, relojes no. La prolongación de la jornada laboral en la agricultura pampeana, de la última dictadura al “boom” sojero - Villulla, Juan Manuel (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2014)
This article analyses the economic mechanisms and discourse devices used by the employers to impose the prolongation and intensification of working time in the pampa ´s agriculture, as well as its consequences on the work conditions of rural workers after the 1970 decade. The methodology includes the query of bibliographic material; employers documentary sources (archives of FACMA); tradeunionism documents (archives of the CGT and UATRE); labour legislation; acts of negociations beetween workers and employers (CNTA and CAR); journalistic material; and testimonies collected over a sample of 50 rural workers and 20 employers in some of the typical departments of the soya-beans “boom” of the last years in the provinces of Buenos Aires, Santa Fe, and Córdoba. The result of our analysis invites to incorporate as one of the conditions of possibility for the recent agricultural expansion an increase of the exploitation of the wage earn workers